ANALYSIS OF THE ADVANTAGES AND DISADVANTAGES OF OUTSOURCING: ANALYSIS OF THE ADVANTAGES AND DISADVANTAGES OF OUTSOURCING - Yankova –Yordanova, Yordanka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
With outsourcing growth expected in the years to come, it is time to learn more about this topic. Before we move forward, it’s imperative to compare the pros and cons of outsourcing. And it's also very important to understand the effect outsourcing can have on companies.